Semantic Annotations for Workflow Interoperability (Informatica, 2014)
To support the interoperability or the cooperation between different partners, various approaches andtechnological solutions were proposed, which converge directly to the adoption of standards.Consequently, the semantic aspect is not correctly addressed by today's interoperability solutions thatfocus mainly on the syntactical and technical level. Indeed, addressing the semantic aspect atconceptual level will provide more flexibility to the cooperation. Accordingly, in this paper, we proposean agnostic approach for the interoperability of Workflow models (or business process), which is usedin a homogeneous or in a heterogeneous context. In a homogeneous context, lexical and structuralannotations are attached to models. Contrary, in a heterogeneous context, we introduce a commonsemantic annotation structure for annotating the models at different levels: 1) meta-models, 2) modelscontent, 3) models profiles and goals for semantic discovery purposes, 4) at levels of basic aspects ofmodels such as the informational type. Common ontologies, including: Workflow ontology, domainspecific ontology, profiles ontology, goals ontology and a set of ontologies related to these aspects, areused to achieve semantic interoperability. One of the advantages of this proposal is its flexibility and itsopenness since we take an agnostic approach to ontology representation languages (such as OWL-S orWSDL-S).